“I come from a country that is no more”: Jewish nostalgia in the postcolonial Mediterranean - Miccoli, Dario (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2017)
Based upon a corpus of literary texts by Jewish authors born, or descendants of families that lived in North Africa and Egypt and that in the 1950s and 1960s migrated to Israel, France or Italy, the essay looks at nostalgia as a foundational trope in the Mediterranean Jewish historical imagination. Nostalgia is analyzed as a literary chronotope, that allows these writers to come to terms with a complex and ambivalent past while, at the same time, reflecting upon its repercussions on the postcolonial present and future. What comes out is an original archive of memories travelling across the Mediterranean, that while shedding light on the ruptures and continuities between colonial and postcolonial times, reflects on the possibilities of coexistence and reconciliation – or, on the other hand, on the cleavages – that still exist between Jews and Arabs, Europe and North Africa, the Diaspora and Israel.